"Gádeira", el décimo trabajo de Heracles y la política de Atenas - Fernández Camacho, Pamina (2013)
The myth of Herakles and Geryon is important to understand the Greek conception of the Far West. In V and IV century B.C. Athens, it was given a political signification which aligned with Athenian aspirations to control the West as far as the Pillars of Herakles. In this article, we study this political use of the myth and its implications, analyze its origin in the circle of Cimon of Athens, its influence on the literary representation of the island of Gadeira, and the criticism of its intent implicit in Plato’s Atlantis myth.
Keywords: Hércules (Personaje mitológico); Política; Atenas (Grecia)